Phytochemistry, bioactivities, and future prospects of Callicarpa nudiflora: A review - Yan Ma; Licheng Guo; Wencheng Hou; Jinsheng Zhuo; Mingming Zhao; Yangyang Liu (Medicinal Plant Biology, 2022)
Callicarpa nudiflora is a regional medicinal herb in China. A typical tropical rainforest medicinal plant, it is processed in China's Hainan province, Guangdong province and Guangxi Zhuang Autonomous Region, as well as India, Vietnam, Malaysia and Singapore. C. nudiflora has the functions of clearing away heat, detoxification and dampness. Flavonoids, phenylpropanes, terpenoids and volatile oils as well as phenols and sterols are the main chemical constituents. Modern pharmacology shows that C. nudiflora has anti-inflammatory, hemostatic, antibacterial, and hepatoprotective effects, treats breast and colon cancer, and is clinically used to treat tropical bacterial infections, acute infectious hepatitis, and internal and external bleeding. C. nudiflora is different from traditional herbal medicines because it has significant anti-inflammatory and hemostatic effects and is widely used as a single prescription medicine. This review evaluates recent advances in fully determining the chemical composition and pharmacological effects of C. nudiflora, thereby laying the foundation for future pharmaceutical research.